PENGARUH OBESITAS TERHADAP SIKLUS MENSTRUASI PADA REMAJA DI DESA RAMBAH TENGAH HILIR KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Rahmi Fitria (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
The menstrual cycle is the distance between the start date of the last menstrual period and the start of the next menstruation which occurs repeatedly every month. Regular cycles every month with a span of 21 to 35 days each menstrual period and the length of menstruation lasts 3-7 days. Menstrual cycle abnormalities are a sign of some abnormalities in the cervix, uterine cancer, breast cancer, and infertility. There are several factors that affect the menstrual cycle such as physical activity, stress, diet, hormonal factors, food consumed, enzymes in the body and BMI. Menstrual cycle can be influenced by body weight, physical activity, stress level, and ovarian disorders. This research uses a descriptive method, which is a research method that describes certain variables in research with a cross-sectional design. The population is 287 people. Samples obtained by accidental technique obtained 32 teenagers. The results of this study showed that the average data for adolescents with BMI 29.29 ± 3.3 had abnormal menstrual cycles. The statistical test results obtained a p value of 0.025, which means that there is an influence between obesity on the menstrual cycle in adolescents